Trends in the Diagnosis of Gestational Diabetes Mellitus - Surabhi Mishra; Chythra R. Rao; Avinash Shetty (Scientifica)
Introduction. Gestational diabetes mellitus (GDM) is defined as carbohydrate intolerance of variable degree with onset or recognition during pregnancy. As prevalence of diabetes is linked to impaired glucose tolerance during antenatal period, routine antenatal screening of GDM is required. However, screening tests for GDM remain controversial. Objective. To review different diagnostic criteria for GDM. Materials and Methods. Freely accessible, full-text articles from 1964 to 2015, available in PubMed in English language, pertaining to screening of GDM were reviewed. Results. First diagnostic criteria for GDM in 1964 by O’Sullivan and Mahan, modified by the National Diabetes Data Group (NDDG) in 1979 and Carpenter in 1982. The cut-off value as per WHO definition of GDM was 140 mg/dL, 2 hours after 75 g glucose intake. Diabetes in Pregnancy Study Group India (DIPSI), in 2006, endorsed WHO criteria but irrespective of the last meal timings. Being cost-effective, it formed the basis of national guidelines for Indians in 2014. Conclusions. As typical clinical scenarios are usually varied, practical guidelines that meet the constraints of low-resource settings like India are required.